SPIRITUALITY AS A FOUNDATION FOR SME RESILIENCE IN THE CONSTRUCTION SECTOR: EVIDENCE FROM MALAYSIAN OGSE SMES - Surin, Rus Sumariyanti; Kamaruding, Musmuliadi; Abang Muis, Abang Mohd Razif (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2026)
Small and medium-sized enterprises (SMEs) operating in project-based industries such as the construction sector and the oil and gas services and equipment (OGSE) sector often face market instability, uncertain operating environments, and limited resources. This affects the resilience of the company and forces it to modify its structure, strategy, and operational practices to survive in the market. Past studies are seen to pay less attention to ethical and value factors and spirituality as factors of organizational resilience when facing a crisis. Therefore, this study aims to explore the aspect of spirituality as a source of resilience among Malaysian OGSE SMEs and examine how it can be applied in the construction sector. Guided by a qualitative research approach, semi-structured interviews were conducted with seven SME leaders who met clear criteria, including a minimum of ten years of business experience and compliance with PETRONAS licensing requirements. The thematic analysis revealed that there are three interconnected spiritual values, namely the charity, religion, and honesty, as practices, which are significant to organizational resilience. These values should be incorporated in the leadership practices, workplace culture, and crisis management practices. Their philanthropic engagements, particularly the zakat and social engagement fostered social affiliations, and sparked off organizational legitimacy. In the meantime, the religious practices provided mental relaxation, moral support and solidarity during uncertain periods and the concept of honesty was defined as the source of trust, transparency and sustenance of long-term relations with stakeholders. In general, this paper can be related to the literature on resilience because it shows that spirituality is a practical and value-based approach that enhances organisational stability and stakeholder trust, which has provided construction SMEs with a culturally based avenue through which they can improve resilience in unstable and risky contexts.